Advances in contemplative psychotherapy accelerating personal and social transformation - Brandon, Fiona; Neale, Miles; Wolf, Emily J.; Loizzo, Joseph John 1955- (Routledge, 2023)
"Advances in Contemplative Psychotherapy offers mental health professionals of all disciplines and orientations the most comprehensive and rigorous introduction to the art of integrating contemplative psychology, ethics, and practices including mindfulness, compassion, and embodiment techniques. It brings together clinicians, scholars, and thought leaders of unprecedented caliber, featuring some of the most eminent pioneers in the rapidly growing field of contemplative psychotherapy. The new edition offers an expanding array of effective contemplative interventions, contemplative psychotherapies, and contemplative approaches to clinical practice. New chapters discuss how contemplative work can effect positive psycho-social change at personal, interpersonal, and collective levels to address racial, gender, and other forms of systemic oppression. The new edition also explores the cross-cultural nuances in the integration of Buddhist psychology and healing practices by Western researchers and clinicians and includes the voices of leading Tibetan doctors. Advances in Contemplative Psychotherapy offers the most profound and synoptic overview to date of one of the most intriguing and promising fields in psychotherapy today"-- Provided by publisher.